2022
DOI: 10.21037/atm-22-1112
|View full text |Cite
|
Sign up to set email alerts
|

ASPM and TROAP gene expression as potential malignant tumor markers

Abstract: Background: Although increasing evidence supports a vital role for assembly factor for spindle microtubules (ASPM) and trophinin-associated protein (TROAP) in the tumorigenesis of some cancers, no systematic pancancer analyses of ASPM and TROAP have been performed. Thus, we aimed to investigate the potential functions of ASPM and TROAP across 31 cancer types.Methods: Based on datasets from The Cancer Genome Atlas (TCGA), Human Protein Atlas (HPA), Gene-Cloud of Biotechnology Information (GCBI) and Gene Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…TROAP can affect tumor progression through various pathways; for example, it can promote disease progression through the Wnt3/survival protein signaling pathway in prostate cancer [16]. In addition, Han Liu et al found that TROAP regulated cell division cycle 20 (CDC20) and influenced spindle microtubules (ASPM) to promote malignant tumor development during the S and G2 phases of the cell cycle [17]. Lastly, TROAP can be used as the target of some microRNAs to inhibit the proliferative activity of cancer cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…TROAP can affect tumor progression through various pathways; for example, it can promote disease progression through the Wnt3/survival protein signaling pathway in prostate cancer [16]. In addition, Han Liu et al found that TROAP regulated cell division cycle 20 (CDC20) and influenced spindle microtubules (ASPM) to promote malignant tumor development during the S and G2 phases of the cell cycle [17]. Lastly, TROAP can be used as the target of some microRNAs to inhibit the proliferative activity of cancer cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Notable among the therapeutic target genes associated with breast cancer identified through this approach with the LOG model are TFPI2 [27][28][29], TROAP [30][31][32][33], and TONSL [34][35][36]. In the MLP model, critical genes such as TNNT1 [37,38] and AQP7 [39][40][41] were also identified as potential therapeutic targets.…”
Section: Biological Relevancementioning
confidence: 99%
“…For example, the microcephaly gene DONSON encodes a replication fork protein that maintains genome stability by stabilizing stalled forks and activating replication checkpoints (Reynolds et al, 2017). Several bioinformatic methods have indicated that ASPM, along with its upstream regulator trophinin-associated protein (TROAP) and downstream factor cell division cycle 20 (CDC20), may regulate cell replication during the S and G2 cell cycle phases; however, details of the mechanism involved remain unknown (Liu et al, 2022). Recently, a study carried out by our group in HeLa cells uncovered the function of ASPM in maintaining genome stability in response to replication stress .…”
Section: Aspm In Dna Replicationmentioning
confidence: 99%